2008
DOI: 10.1063/1.2816749
|View full text |Cite
|
Sign up to set email alerts
|

A vacuum ultraviolet laser photoionization and pulsed field ionization study of nascent S(P2,1,3) and S(D21) formed in the 193.3nm photodissociation of CS2

Abstract: The photoionization efficiency (PIE) and pulsed field ionization-photoion (PFI-PI) spectra for sulfur atoms S(3P2,1,0) and S(1D2) resulting from the 193.3 nm photodissociation of CS2 have been measured using tunable vacuum ultraviolet (vuv) laser radiation in the frequency range of 82 750-83 570 cm(-1). The PIE spectrum of S(3P2,1,0) near their ionization threshold exhibits steplike structures. On the basis of the velocity-mapped ion-imaging measurements, four strong autoionizing peaks observed in the PIE meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 35 publications
6
25
0
Order By: Relevance
“…This structure was also observed by Pan and co-workers [23] at a wavenumber of 75 821 cm −1 (corresponding to 9.401 eV) and by Yang et al [21,22] for a wavenumber of 75 818 cm −1 (corresponding to 9.400 eV). Pan et al [23] discussed an assignment to a 1 G series, but because of ∆J = 2 this was excluded.…”
Section: Sulfursupporting
confidence: 59%
See 4 more Smart Citations
“…This structure was also observed by Pan and co-workers [23] at a wavenumber of 75 821 cm −1 (corresponding to 9.401 eV) and by Yang et al [21,22] for a wavenumber of 75 818 cm −1 (corresponding to 9.400 eV). Pan et al [23] discussed an assignment to a 1 G series, but because of ∆J = 2 this was excluded.…”
Section: Sulfursupporting
confidence: 59%
“…Waller et al reported a branching ratio S( 3 P J )/S( 1 S J ) = 2.8 ± 0.3 [83] and 1.6 ± 0.3 was reported by Xu et al [19], also in favor of S( 3 P ). However, the present value of 2.8 ± 0.4 in favor of the S(3s 2 3p 4 1 D) state agrees with that found by Yang et al [21,22]. There is no plausible explanation for the large discrepancy in the experimental values for the branching ratio of S(3s 2 3p 4 1 D) to S(3s 2 3p 4 3 P ) from the 193 nm (6.424 eV) photolysis of CS 2 .…”
Section: Photoionization Of S(3ssupporting
confidence: 57%
See 3 more Smart Citations